Toward a Criminology of Terrorism - LaFree, Gary (Elements in Criminology, 2023)
In the space of just two decades, research on terrorism and political extremism went from a relatively uncommon niche to a widely recognized criminological specialization. This Element considers the ways that criminology has contributed to the study of terrorism and the impact the increasing interest in terrorism has had on criminology.